Transformation of the Feminine Self in Yogamāyā - Mishra, Indira Acharya (JODEM: Journal of Language and Literature, 2019)
This article aims to analyze the struggle of Yogamaya, the lead female character of the novel Yogamāyā, by Neelam Karki Niharika. The novel based on the real life story of a rebel, Yogamaya, chronicles the incidents of her life that triggered her to cast off her feminine self and rebel for the establishment of a just society based on equity. The article examines those factors that force Yogamaya to rebel against the existing society and the process of her rebellion drawing insights form Helen Cixous and other feminists who find patriarchal gender roles based on binary opposition as oppressive, and suggest that women should act beyond gender binary and subvert the patriarchal norms and values that restrict them in every walk of their lives. I use transliteration and free translation while citing from the novel in the analysis. The finding of the article suggests that a number of factors instigate Yogamaya cast of her feminine self and emerge as a rebel. It helps to understand how Yogamaya subverts patriarchy within its bound exposing the inherent biasness in it.